Study of the influence of topical application of Persantine on the condition of the oral mucosa of rats under the conditions of systemic action of pathogenic factors - M. I. Balega; S. A. Schneider; V. A. Borodach; E. K. Tkachenko (Kazimierz Wielki University, 2018)
Purpose of the study. The study of the protective role of the рersantine when topically applied to the condition of the oral mucosa of rats under conditions of systemic exposure to the fluorine toxicant against the background of polyphenolic insufficiency. Materials and methods. The experiment was conducted on 21 white rat-male 2 months ages that were distributed over 7 animals in a group. The 1st group is intact, the rats were fed on the vivarium diet. In the second group (control oh) in rat bespolifenolnogo background ration was prepared 5 times in week 5% fluorouracil solution per os at a dose of 12.5 mg / kg body weight of rats. The third group, under the combined effect of fluorouracil under the conditions of a bespolyphenol regimen, received topically as a part of a gel, рersantine in a dose of 0.5 mg / kg 5 times a week. Gel - freshly prepared 7.5% potato starch was applied topically to the oral mucosa of the rats. Results and conclusions. introduced against the background of the genotoxicant of fluorouracil in the alimentary deficiency of plant components , manifested in the oral mucosa antioxidant and anti-inflammatory effects. Under the influence of the chimes, the state of the vessels of the microvasculature was normalized due to a significant decrease in edema - the packing density of the vessels and the coefficient of preservation of their lumen increased. There are data on the effect of various toxicants with a lack of plant food components on the occurrence of dental pathology [3].